Meaning of work from the perspective of hospital nurses - Meirieli Faza Franco; Beatriz Francisco Farah; Simone Coelho Amestoy; Maira Buss Thofehrn; Adrize Rutz Porto
ABSTRACT Objectives: to know the meaning of the role of nurses in the hospital environment. Methods: this is a descriptive study with a qualitative approach, whose setting was a university hospital in Minas Gerais with 50 nurses. Data were collected through interviews and analyzed according to content analysis, with the contribution of the Interface software from R pour les Analyzes Multidimensionalnelles de Textes et de Questionnaires. Results: three categories emerged: "Nurses' daily work in the hospital environment"; "Work motivation as an influential factor in the meaning of work"; "The two faces of the meaning of work: pleasure and suffering". Nurses attributed a positive meaning to their work. Final Considerations: three dimensions of the meaning of work were highlighted: individual, organizational and social. These influenced the professional, social, working and individual life of nurses.